Pelatihan Bahasa Inggris Berekuivalensi Toefl Bagi Pelaku Wisata Di Istana Maimun - M Mayasari; Z Zuindra; A Arifuddin; Muhammad Kiki Wardana (Jurnal TUNAS, 2022)
This training is carried out to provide understanding and knowledge to the society, especially tour guides who are at Istana Maimun. The purpose of this community service is training for the TOEFL (Test of English Foreign Language). In addition, it provides understanding and knowledge of the TOEFL (Test of English Foreign Language). It is hoped that the results of this training can provide new understanding and knowledge about the TOEFL (Test of English Foreign Language) to other people. This activity is carried out using lecture and discussion methods. The lecture method is used in the process of delivering training/socialization materials. The expected output targets of this activity are: 1) Tour guides know what the TOEFL (Test of English Foreign Language) is, 2) Tour guides understand the types of questions tested in the TOEFL (Test of English Foreign Language), 3 ) Tour guides understand the tips and tricks for doing the TOEFL (Test of English Foreign Language) questions, and 4) Tour guides are able to work on the questions tested in the TOEFL (Test of English Foreign Language).